Cytotoxicity Study Of MCF-7 Breast Cancer Cell Lines Treated With Physalis Minima L. Extract - Jaafar, Nurul Izzati (2019)
Physalis minima L. is believed for having a wide range of biological activities such as anti-cancer and antioxidant properties. In this study, the effect different solvents of several degree of polarities; hexane (P-Hex), dichloromethane (P-DCM), chloroform (CHCl3), n-butanol (P-nBuOH), aqueous (P-Aq) and crude methanolic (CMeOH) on the anti-cancer activity of MCF-7 cells were studied. P-DCM extract exhibited as a potent anti-cancer agent with inhibition of 50% at 24 μg/ml on MCF-7 cells and non-toxic towards MCF-10A normal cells. Analysis of cell death mechanism revealed that the extract induced apoptotic programmed cell death in MCF-7 cells with typical chromatin condensation and apoptotic body formation, which are the biochemical hallmark of apoptosis. Different stage of apoptotic programmed cell death together with phosphatidylserine externalization were established using annexin V and propidium iodide staining. Besides that, acute exposure of the extract on MCF-7 cells produced a significant up-regulation of p53 and Caspase 8 expression, suggested that extrinsic pathway was involved. Besides that, P-DCM extract was examined for the antioxidant properties. The total phenolic that contained in the extract was recorded as 75390 μg Gallic acid equivalents/g while the flavanoids was 2480 μg of Quercetin equivalents/g. Moreover, the extract showed as strong scavenger with IC50 value of 2.2 μg/mL in DPPH and 8.64 μg/mL in ABTS.